1984
DOI: 10.1056/nejm198411223112105
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmissions in the Medicare Population

Abstract: In order to examine the proportion of Medicare expenditures attributable to repeated admissions to the hospital, we assessed the frequency with which 270,266 randomly selected Medicare beneficiaries were readmitted after hospital discharge between 1974 and 1977. Twenty-two per cent of Medicare hospitalizations were followed by a readmission within 60 days of discharge. Medicare spent over $2.5 billion per year (24 per cent of Medicare inpatient expenditures) on such readmissions between 1974 and 1977. Analogou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
209
4
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(225 citation statements)
references
References 0 publications
6
209
4
2
Order By: Relevance
“…Our analyses show that the mix of beneficiaries served at the hospitals affects readmission rates. For example, consistent with Anderson and Steinberg [14] , readmission rates increased by about 0.09 percentage points for each percentage point increase in the share of dual eligible Medicare patients. Similarly, the effect of average risk scores on readmission rates is significant and relatively large: One unit increase in average risk score (e.g., increase from 1 to 2) increases the readmission rate by about 4.9 percentage points.…”
Section: Descriptive Findingssupporting
confidence: 61%
See 1 more Smart Citation
“…Our analyses show that the mix of beneficiaries served at the hospitals affects readmission rates. For example, consistent with Anderson and Steinberg [14] , readmission rates increased by about 0.09 percentage points for each percentage point increase in the share of dual eligible Medicare patients. Similarly, the effect of average risk scores on readmission rates is significant and relatively large: One unit increase in average risk score (e.g., increase from 1 to 2) increases the readmission rate by about 4.9 percentage points.…”
Section: Descriptive Findingssupporting
confidence: 61%
“…Dual eligible beneficiaries (low income and disabled beneficiaries covered by both Medicare and Medicaid) have been found to have significantly higher readmission rates than those with only Medicare coverage [14] . Corrigan and Martin found that individuals covered by Medicare and Medicaid (compared to private insurers) are more likely to be readmitted within a year [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Dranove 2002) have reported that hospitals, like most …nancially oriented entities, have an incentive to increase pro…ts when possible. For instance, Friedman and Pauly (1983) and Anderson and Steinberg (1984) have shown that hospitals exhibit a pro…t-maximizing response to changes in reimbursement terms. In the US, the diagnosis related group (DRG) for the diagnosis of the patient at the time of discharge determines the amount that the hospital is paid (Fed- (Friedman and Pauly 1983).…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…A study from the US calculated that between 1974 and 1977, 24% of Medicare inpatient expenditure was spent on readmissions. 22 This was projected to be about $8 billion in 1984. Therefore even a small decrease in readmissions will result in substantial savings.…”
Section: Discussionmentioning
confidence: 99%
“…HOSPITAL READMISSION RATES have been increasing during the last 5 years in developed [1][2][3] as well as developing countries. 4 Major concerns of readmission are the cost to the health services, financial implications and emotional distress to patients and their families and perpetuating dependency behaviour among patients.…”
mentioning
confidence: 99%